Model Pengadaan CPNS Masa Bencana Nasional Non Alam : Studi Empiris Problematik Proses Bisnis Pengadaan Calon Pegawain Negeri Sipil Pada Masa Pandemik Covid-19 di Kementerian Kelautan dan Perikanan - Dida Daniarsyah; Rusdi Rusdi (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2021)
This article tries to analyze the problems of business processes procurement of Candidate of Civil Servant (CPNS) during the Covid-19 pandemic. The formulation of research problems is that business process services of CPNS at the Ministry of Marine Affairs and Fisheries are less effective during pandemics. Problems found in the field include the inefficiency of time in business processes of recruitment and selection subprocesses. This study uses qualitative descriptive approach with empirical study method at the Ministry of Marine Affairs and Fisheries. Adoption of technology utilization, recruitment and selection procedures based on the needs of priority positions, business process of selection time is not simultaneous, intensive coordination business process between implementing agencies and responsible agencies can be a model of business processes procurement CPNS non-natural national disaster period